Peripheral Blood Platelets Express VEGF-C and VEGF which Are Released during Platelet Activation - Wartiovaara, Ulla; Salven, Petri; Mikkola, Hanna; Lassila, Riitta; Kaukonen, Jaakko; Joukov, Vladimir; Orpana, Arto; Ristimäki, Ari; Heikinheimo, Markku; Joensuu, Heikki; Alitalo, Kari; Palotie, Aarno (Thrombosis and Haemostasis, 1998)
VEGF-C is a recently characterised endothelial growth factor structurally related to vascular endothelial growth factor (VEGF). We studied the expression of VEGF-C and VEGF in the cells of peripheral blood and in the umbilical cord blood CD 34+ cells, representing haematopoietic progenitor cells. Expression of VEGF-C was detected in the CD34+ cells. In peripheral blood VEGF-C mRNA was restricted to platelets and T-cells. In contrast to the expression pattern of VEGF-C, VEGF mRNA was detected in all peripheral blood cell fractions studied, and also in CD34+ cells. VEGF-C mRNA was also detected in fresh bone marrow samples of acute leukaemia patients, but the expression did not show lineage specificity. VEGF-C and VEGF polypeptides were present in platelets and they were released from activated platelets together with the release of β-thromboglobulin, suggesting that VEGF-C and VEGF reside in the α-granules of platelets. VEGF-C and VEGF, released from activated platelets, may have a role in angiogenesis during wound healing, and possibly also in other pathological conditions, such as atherosclerosis, tumour growth, and metastasis formation.